2014
DOI: 10.1128/aac.03570-14
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Reactive Oxygen Species Is a Universal Action Mechanism of Amphotericin B against Pathogenic Yeasts and Contributes to the Fungicidal Effect of This Drug

Abstract: e Amphotericin B (AMB) is an antifungal drug that binds to ergosterol and forms pores at the cell membrane, causing the loss of ions. In addition, AMB induces the accumulation of reactive oxygen species (ROS), and although these molecules have multiple deleterious effects on fungal cells, their specific role in the action mechanism of AMB remains unknown. In this work, we studied the role of ROS in the action mechanism of AMB. We determined the intracellular induction of ROS in 44 isolates of different pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
151
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(175 citation statements)
references
References 92 publications
(95 reference statements)
12
151
0
3
Order By: Relevance
“…The following C. tropicalis strains resistant to AmB were used in this work: ATCC 200956 and CL-6835 (from the yeast collection of the Mycology Reference Laboratory of the Spanish National Centre for Microbiology). The MIC values reported for these strains to AmB and fluconazole were 2 and Ͼ64 mg/liter, respectively (following the EUCAST antifungal susceptibility testing method [9,21]). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following C. tropicalis strains resistant to AmB were used in this work: ATCC 200956 and CL-6835 (from the yeast collection of the Mycology Reference Laboratory of the Spanish National Centre for Microbiology). The MIC values reported for these strains to AmB and fluconazole were 2 and Ͼ64 mg/liter, respectively (following the EUCAST antifungal susceptibility testing method [9,21]). …”
Section: Methodsmentioning
confidence: 99%
“…In this sense, AmB induces ergosterol sequestration, which causes alterations in the cell membrane that result in killing of the cells (3,4). In addition, AmB induces a significant accumulation of reactive oxygen species (ROS), which has been correlated with cell damage, apoptosis induction, and death (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…This complex functions as an ion channel, enhancing the leakage of intracellular K + and other ionic substances. AmBmediated lethality is alternatively attributed to the induction of oxidative stress via the enhanced generation of superoxide anions by this macrolide, as well as to its ability to extract ergosterol from the plasma membrane phospholipid bilayer [2,3]. In previous studies, for the first time, we found that AmB is incorporated across the plasma membrane of fungal cells, resulting in vacuolar membrane disruption with lethal effects [4][5][6].…”
mentioning
confidence: 79%
“…The plates were incubated at 30°C for 2 days and checked for growth. The growth of cells treated with test compounds was compared with that of cells treated with FLC, which is known to be fungistatic, and with that of cells treated with AMB, which is known to be fungicidal (29,30).…”
Section: Methodsmentioning
confidence: 99%
“…284 for fungicidal versus fungistatic activities. This was done in a qualitative assay in parallel with FLC, which is known to be fungistatic (29) and AMB, which is known to be fungicidal (30). The MICs were 3 M (0.9 g/ml), 1.5 M (1.4 g/ml), 12 M, and 0.31 M for FLC, AMB, no.…”
Section: Inhibition Of C Neoformans Growth By Troponoids Antimicrobimentioning
confidence: 99%